Trigeminal Nerve White Matter Fiber Abnormalities in Primary Trigeminal Neuralgia: A Diffusion Spectrum Imaging Study - Luo, Si-ping; Chen, Fan-fan; Zhang, Han-wen; Lin, Fan; Huang, Guo-dong; Lei, Yi (Frontiers in Neurology, 2022)
Objective: Diffusion spectrum imaging (DSI) was used to quantitatively study the changes of trigeminal cistern segment in patients with trigeminal neuralgia (TN), and to further exploring the application value of DSI in patients with TN. Methods: 60 patients with TN and 35 healthy controls (HC) were scanned with conventional MRI and DSI to obtain high-resolution fiber tracking. The patients and the control group were compared within and between groups. The correlation between quantitative parameters of DSI and the visual analogue scale (VAS), symptom duration and responsible vessel types were analyzed. Results: Compared with healthy side in TN group, affected side showed significantly decreased QA(p＜0.001), FA (p=0.001) and GFA (p＜0.001).There were significantly decreased QA (p < 0.001), FA (p =0.001) , and GFA (p < 0.001) and significantly increased AD (p＜0.05) compared the affected side of TN group and the average values of HC group. And there were significant decreased in QA (p < 0.05) and FA (p < 0.01) between the patient's healthy side and the average values of HC group. GFA can evidently distinguish between arteries, veins and healthy side in TN patients. Conclusion: Using high-resolution fiber tracking technology, DSI can provide quantitative information to detect the integrity of trigeminal white matter in patients with TN and can improve the understanding of disease mechanism.